The lost secret a compelling story for English learner - O'Neill, Robert; Shovel, Martin; Orlebar, Jeremy; Sykes, Peter (London : British Broadcasting Corporation, 1986)
It is a mystery drama which forms the basis for a new course designed specifically for adult near-beginners of English
Part 1: ep.1- The beginning; ep.2- Who is he?; ep.3- Who is Sabina; ep.4- Footprints in the sand; ep.5- One o'clock at Alfredo's. Part 2: ep.6- The laboratary; ep.7- Good news and bad news; ep.8-Male and female; ep.9- We have to stop him; ep.10- The red doors; ep.11- The end
Copy available in DVD format
Keywords: English language -- Study and teaching